A new bamboo-feeding planthopper genus Aodingus Chen & Li (Hemiptera: Fulgoroidea: Delphacidae: Tropidocephalini) with descriptions of three new species from China and Vietnam - Li, Hong-Xing; Chen, Xiang-Sheng; Yang, Lin (European Journal of Taxonomy, 2023)
A new planthopper genus, Aodingus Chen & Li gen. nov. and three new species (A. hainanensis Chen & Li gen. et sp. nov., A. obscurus Chen & Li gen. et sp. nov. and A. cuongi Chen & Li gen. et sp. nov.) are described from China and Vietnam. The new genus is superficially similar to Procidelphax Bartlett, 2009 in general appearance in that the body is strongly dorsoventrally flattened. Distinctive features of the new taxon include broadly compressed body with vertex broad, apical margin broadly rounded, middle part concave, median and submedian carinae absent, frons broad and large, wider at base than at apex, forewing broad and long, aedeagus tubular, curved ventrally. A diagnosis for all species, illustrations and an identification key of new genus are provided. A key to the Chinese genera of Tropidocephalini is also provided.